Nigerian government publications, 1966-1973 : a bibliography - Stanley, Janet L. (Ile-Ife, Nigeria : University of Ife Press, 1975)
The book contains all the Federal, regional and state governments of Nigeria which reflect political events and changes in the country with the period under review.
Includes index
usc 18/11/2021
Ref.
Keywords: Government publications; Nigeria